Initial Evaluation of an Electronic Symptom Diary for Adolescents with Cancer - Baggott, Christina; Gibson, Faith; Coll, Beatriz; Kletter, Richard; Zeltzer, Paul; Miaskowski, Christine (JMIR Research Protocols, 2012)
BackgroundThe delivery of optimal care depends on accurate communication between patients and clinicians regarding untoward symptoms. Documentation of patients’ symptoms necessitates reliance on memory, which is often imprecise. We developed an electronic diary (eDiary) for adolescents and young adults (AYAs) with cancer to record symptoms. ObjectiveThe purpose of this paper is to describe the utility of an eDiary designed for AYAs with cancer, including dependability of the mobile application, the reasons for any missing recorded data, patients’ adherence rates to daily symptom queries, and patients’ perceptions of the usefulness and acceptability of symptom data collection via mobile phones. MethodsOur team developed an electronic symptom diary based on interviews conducted with AYAs with cancer and their clinicians. This diary included daily severity ratings of pain, nausea, vomiting, fatigue, and sleep. The occurrence of other selected physical sequelae was assessed daily. Additionally, patients selected descriptors of their mood. A 3-week trial of the eDiary was conducted with 10 AYA cancer patients. Mobile phones with service plans were loaned to patients who were instructed to report their symptoms daily. Patients completed a brief questionnaire and were interviewed to elicit their perceptions of the eDiary and any technical difficulties encountered. ResultsOverall adherence to daily symptom reports exceeded 90%. Young people experienced few technical difficulties and reported benefit from daily symptom reports. Symptom occurrence rates were high and considerable inter- and intra-patient variability was noted in symptom and mood reports. ConclusionsWe demonstrated the utility of an eDiary that may contribute insight into patients’ symptom patterns to promote effective symptom management.